Comparative Study of the Endocrine Disorders of Βeta-Thalassemia Major Patients and Control Group in Duhok Province - Ali, Ghorbat S.; Jubrial, Amad M.S.; Najeeb, Malika K.; Al hussein, Hamdia Y.I. (Science Journal of University of Zakho, 2018)
Beta- thalassemia major  is a type of inherited blood disorder, characterized by impaired  synthesis of the beta chains. Currently, blood transfusion and sufficient iron chelation therapy are important for treatment and follow up of thalassemia patients. Unfortunately, repeated blood transfusion causes the progressive iron overload. Consequently, the excess iron is deposited as hemosiderin and ferritin in the tissues and multiple endocrine complications. In comparison with healthy control group, the results indicated significant (p
Keywords: β-Thalassemia; FT4; TSH; Estradiol; Testosterone